Na pisada feminina do coco cearense: saberes, lutas, batuques ancestrais e contemporâneos - Masullo, Alessandra Savia da Costa (2015)
This paper aims to analyze, in a racial ethnic and gender perspective, the meanings of the Coconut game for the women from Coco da Batateira in Crato -CE, and its relation to the Africanities, identifying some markers of this culture in their speeches and the confects (concepts loaded of affection) prepared by them. The activities were carried out with the researcher-group made up of ten women members of the group "Women of the Coco da Batateira", all aged between 50 and 80 years. The research was conducted with the Sociopoética approach, in which the production of the data occurs in the experience of workshops that use the whole body in the construction of collective knowledge, by performing techniques involving art and creativity. Were performed the Parangolé technique and Terreira da of the four elements, device created by me for this work. To perform the analyzes, a dialogue was conducted with several scholars as Maria Ignez Ayala (2000), Juliana Bittencourt Manhães (2010), as Graziela Rodrigues (1997), Shara Jane Holanda Costa Adad (2005), Sandra Haydée Petit (2002; 2010), Cícera Nunes (2011), Albernaz (1996; 2006), Scott (1996), Wlamira R. de Albuquerque and Valter Fraga Filho (2006), Ninno Amorim (2007), Ridalvo Félix deAraujo (2013), Hampaté Bâ (1982), José Jorge Carvalho (2000; 2004) Eduardo Socha (2007), Janote Pires Marques (2009), Eurípedes Funes (2004), Eduardo Oliveira (2003; 2007), Henrique Cunha (2001; 2005), Jacques Gauthier (2005; 2012), among others. At the end of this paper, I present the research conclusions, and, among them, the recognition and the reaffirmation of the importance of the Coconut as an axis of formation and structure of the lives of those women that, every day, compose the Coco da Batateira.